PRINSIP-PRINSIP HUKUM DAN BENTUK PENYELESAIAN SENGKETA KONTRAK DAGANG INTERNASIONAL - Tata Eliestiana Dyah A; Jamaludin, Jamaludin (RETORIKA: Journal of Law, Social, and Humanities, 2024)
Abstract International business contracts regulate the legal relations of parties across countries within different legal systems, potentially creating legal uncertainty if not carefully formulated. The existence of a choice of law clause is a crucial element in international trade contracts to ensure legal certainty, provide protection for the parties, and prevent future disputes. This study aims to analyze the legal principles underlying international trade contracts and examine the dispute resolution mechanisms used in international business contract practice. This study uses a normative legal research method with a statutory and conceptual approach. The legal materials used include primary, secondary, and tertiary legal materials. The collection of legal materials was carried out through literature studies, with legal material analysis using the legal interpretation method. The research findings show that the principles of international commercial contract law, including party autonomy, choice of law, and good faith, serve as the foundation for ensuring legal certainty and balancing the interests of parties across jurisdictions. Supporting principles such as lex loci contractus, real connection, and separability clauses ensure legal enforceability when the choice of law is unclear or the contract is disputed. In dispute resolution practice, litigation and ADR mechanisms are strategically applied, with arbitration occupying a primary role due to its final, binding, and easily enforceable cross-border nature, while mediation and other forms of ADR serve as cooperative mechanisms to maintain business relationships. The integration of these principles with dispute resolution mechanisms underscores the importance of legal norm harmonization and contractual efficiency in international commercial transactions.